Indian summer monsoon and winter hydrographic variations over past millennia resolved by clay sedimentation - Chauhan, Onkar S.; Dayal, A.M.; Basavaiah, N.; Kader, U. Syed Abdul (My University, 2010)
Reconstruction of century‐scale Indian monsoon and winter hydrography is made from an AMS‐dated core located in the unique region of the southeast Arabian Sea which lies in the pathways of the lowsalinity Bay of Bengal Waters, advecting during winter northeast monsoon (NEM). Based upon clay mineral analyses in seawaters, we identify chlorite and kaolinite as specific clays supplied by the Bay of Bengal Waters and local fluvial flux (by the southwest monsoon (SWM) precipitation from the Peninsular India), respectively, along the southwest continental margin of India. An evaluation of clay flux and d18O in G. ruber portrays century‐scale weaker SWM precipitation events during ∼450–650 yr, ∼1000 yr, and 1800–2200 cal yr BP. Kaolinite wt % and flux were found to be low during all these events, though chlorite had a persistent or enhanced flux. From the enhanced flux of chlorite and reduced kaolinite/chlorite ratio, during weaker phases of SWM, we deduce a stronger NEM (winter hydrography), implying an inverse coupling between the summer and the winter monsoon.
Keywords: Indian summer monsoon; Indian winter hydrographic; Bay of bengal waters; Clay sedimentation